Translation and adaptation of satisfaction with amplication in daily life (SADL) questionnaire into Malay - Ramli, Afira Nadia; Wan Ahmad, Wan Aslynn Salwani; Mohd Sakeri, Nurul Syarida; Mohamed Zain, Nor Azrita (2018)
In the recent decades, the level of satisfaction with amplification among hearing aid users has been one of the major interesting research subjects. This preliminary study was aimed to evaluate the level of satisfaction with amplification among hearing aid users particularly among the Malay speakers. In order to achieve the aim, the SADL questionnaire was adapted from Cox, Alexander, & Cox (1999). The original SADL questionnaire was translated and validated into Malay language in order to be used for data collection. Several issues were identified during the process of translation A total sample of 15 hearing aid users (first time and experienced) was involved in this study. The result showed that the Malay SADL is valid and reliable to assess the level of satisfaction among hearing aid users. It was found that the device-related factors, audiologist competence, and psychoacoustic and psychological benefit from the hearing aid are the important component that can influence the level of satisfaction among hearing aid users. In conclusion, the Malay SADL can be used as a clinical tool in assessing the level of satisfaction with amplification in daily life.